Desain Pembelajaran Flipped Classroom Dengan Model Pembelajaran Bela H. Banathy di Lembaga Pendidikan Islam - Mohammad Kurjum; Leily Indah Faizah; Fairuz Dianah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Nowedays the technological development had been spreaded in many areas, especially in education, changed from old toward new system. Based on this phenomena, the researcher wanted to identify the strength and the weaknesses in undertaking of the application of Flipped classroom learning model on the subject of Aqidah Akhlaq toward students of MA Raudlotul Banat Sidoarjo. The problems are the students had spared their times using gadget or the other technological tools not to develop their academic achievement. This research aims at implementing descriptive qualitative methods. The research had planned to conduct Flipped Classroom implementation in collaboration with Bela H. Bahathy learning.